1993
DOI: 10.1677/joe.0.1390107
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and immunological characterization of oestrogen receptor in the cytosolic fraction of gluteal, omental and perirenal adipose tissues from sheep

Abstract: Determination of the presence and characterization of oestrogen receptors (ERs) in subcutaneous and internal fat depots were performed and compared with ERs in the uterus using ligand binding and immunological techniques. Successful and consistent measurement of ERs in ovine adipose tissue could only be accomplished in animals depleted of endogenous sex steroids by combined ovariectomy and adrenalectomy. Scatchard, sucrose gradient and Western blot analyses all confirmed the presence of ERs in the cytosolic fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 18 publications
(22 reference statements)
2
15
0
Order By: Relevance
“…In past studies, ERs could not be demonstrated with routine binding assays because of the high nonspecific binding of estrogens stored in adipose tissue (14). With the development of more sensitive assays, ER mRNA (by PCR and Northern blot analysis) and ER protein (8,9) have been demonstrated in human adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…In past studies, ERs could not be demonstrated with routine binding assays because of the high nonspecific binding of estrogens stored in adipose tissue (14). With the development of more sensitive assays, ER mRNA (by PCR and Northern blot analysis) and ER protein (8,9) have been demonstrated in human adipose tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Direct action of estrogens in adipose tissue is supported by the presence of both receptor isoforms ␣ and ␤ (94, 124). Sex-and depotrelated differences in estrogen receptor levels have been reported, but the data remain unclear (54,124,421,609). Interestingly, deletion of the estrogen receptor ␣ in male and female mice is associated with increased adiposity independent of food intake (216).…”
Section: Sex Hormonesmentioning
confidence: 99%
“…Oestrogen receptor (ER) was present in adipose tissues from these animals (Watson et al 1993) and the ER appeared to be functional as oestrogen treatment of ovariectomized ewes resulted in the up-regulation of progesterone receptor (PR) in adipose tissues (Mayes et al 1996). This study is our initial investigation into the presence of AR in omental adipose tissue from female sheep.…”
Section: Introductionmentioning
confidence: 95%
“…Omental adipose tissue (1 g/ml) was homogenized at 4 C with Medium I (0·25 M sucrose, 1 mM EDTA, 10 mM Tris-HCl, pH 7·4) which contained protease inhibitors (aminoethyl-benzenesulfonyl fluoride, leupeptin, bacitracin, aprotinin and pepstatin; Watson et al 1993). Unless otherwise stated, all chemicals and reagents were obtained from Sigma (St Louis, MO, USA).…”
Section: Isolation Of Subcellular Fractionsmentioning
confidence: 99%